The increased presence of repetitive motifs in the KDDR-plus recombinant protein, a kinesin-derived antigen from Leishmania infantum, improves the diagnostic performance of serological tests for human and canine visceral leishmaniasis. - Williane Fernanda Siqueira (Public Library of Science (PLoS), 2021)
Visceral leishmaniasis (VL) is caused by protozoa belonging to the Leishmania donovani complex and is considered the most serious and fatal form among the different types of leishmaniasis, if not early diagnosed and treated. Among the measures of disease control stand out the management of infected dogs and the early diagnosis and appropriate treatment of human cases. Several antigens have been characterized for use in the VL diagnosis, among them are the recombinant kinesin-derived antigens from L. infantum, as rK39 and rKDDR. The main difference between these antigens is the size of the non-repetitive kinesin region and the number of repetitions of the 39 amino acid degenerate motif (6.5 and 8.5 repeats in rK39 and rKDDR, respectively). This repetitive region has a high antigenicity score. To evaluate the effect of increasing the number of repeats on diagnostic performance, we designed the rKDDR-plus antigen, containing 15.3 repeats of the 39 amino acid degenerate motif, besides the absence of the non-repetitive portion from L. infantum kinesin. Its performance was evaluated by enzyme-linked immunosorbent assay (ELISA) and rapid immunochromatographic test (ICT), and compared with the kinesin-derived antigens (rKDDR and rK39). In ELISA with human sera, all recombinant antigens had a sensitivity of 98%, whereas the specificity for rKDDR-plus, rKDDR and rK39 was 100%, 96% and 71%, respectively. When evaluated canine sera, the ELISA sensitivity was 97% for all antigens, and the specificity for rKDDR-plus, rKDDR and rK39 was 98%, 91% and 83%, respectively. Evaluation of the ICT/rKDDR-plus, using human sera, showed greater diagnostic sensitivity (90%) and specificity (100%), when compared to the IT LEISH (79% and 98%, respectively), which is based on the rK39 antigen. These results suggest that the increased presence of repetitive motifs in the rKDDR-plus protein improves the diagnostic performance of serological tests by increasing the specificity and accuracy of the diagnosis.